2020
DOI: 10.1109/access.2020.3035961
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Assisted Detection for Index Modulation Aided mmWave Systems

Abstract: In this paper, we propose deep learning assisted detection for index modulation millimeter wave (mmWave) systems, where we train a neural network (NN) to jointly detect the transmitted data and index information without relying on explicit channel state information (CSI). As a design example, we first employ multi-set space-time shift keying (MS-STSK) combined with beamforming for transmission over the mmWave channel, where the information is conveyed implicitly using the index of the antennas, the dispersion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…, where ρ t is the pilot transmission power and τ p represents the pilot symbols¡ transmission duration [46]. In Fig.…”
Section: Number Of Configurable Impedancesmentioning
confidence: 99%
“…, where ρ t is the pilot transmission power and τ p represents the pilot symbols¡ transmission duration [46]. In Fig.…”
Section: Number Of Configurable Impedancesmentioning
confidence: 99%
“…In [27], the authors presented and demonstrated the index modulation millimeter wave (mm wave) systems by the utilization of deep learning assisted detection. Here concurrently detection of transmission and index information are performed by a neural network (NN) that is not reliant on on explicit channel state information (CSI).…”
Section: Index Modulation Aided MM Wave Systems Based On Detection By Deep Learning Assisted Methodsmentioning
confidence: 99%
“…In this direction, several researcher have focused on presenting ML-related solutions for automatic modulation recognition (AMR) (Khan et al, 2016;Li et al, 2018;Wu et al, 2018;Iqbal et al, 2019;Shah et al, 2019;Yang et al, 2019;Bu et al, 2020), channel estimation (Satyanarayana et al, 2019;Zhu et al, 2019;Liu S. et al, 2020;Ma et al, 2020a;Ma et al, 2020b;Moon et al, 2020;Mai et al, 2021;Wang et al, 2021), and signal detection (Jeon et al, 2018;Aoudia and Hoydis, 2019;Samuel et al, 2019;Katla et al, 2020;Satyanarayana et al, 2020). In more detail, AMR has been identified as an important task for several wireless systems, since it enables dynamic spectrum access, interference monitoring, radio fault self-detection as well as other civil, government, and military applications.…”
Section: Phy Layermentioning
confidence: 99%
“…In this sense, in (Samuel et al, 2019), the authors employed a DNN architecture for data detection, whereas, in (Aoudia and Hoydis, 2019), the effectiveness of deep learning for end-to-end signal detection was reported. Similarly, in (Katla et al, 2020), the authors presented a deep learning assisted approach for beam index modulation detection in high-frequency massive MIMO systems. Additionally, in (Satyanarayana et al, 2020), the authors demonstrated the use of deep learning assisted soft-demodulator in multi-set space-time shift keying millimeter wave (mmW) wireless systems.…”
Section: Phy Layermentioning
confidence: 99%
See 1 more Smart Citation